CULTURAL DIMENSIONS INFLUENCING THE SUCCESS OF INTERNATIONAL FRANCHISING (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis presents a comprehensive systematic review of the cultural dimensions influencing the success of international franchising, synthesizing over 400 peer-reviewed studies, empirical analyses, and case studies from 2000 to 2025. It explores how cultural factors, framed through models like Hofstede’s dimensions and the GLOBE project, mediate franchise adaptation, performance, and sustainability across global markets. Key themes include consumer behavior adaptations, franchisee-franchisor relationships, and risks of cultural misalignment, with new insights into emerging markets such as Uzbekistan. The review highlights opportunities for cultural hybridization and advocates for culturally intelligent strategies to enhance global franchising outcomes, while identifying research gaps for future investigations.